2012
DOI: 10.1002/jsfa.5698
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, nutritional and toxicological evaluation of rice (Oryza sativa) grown in fly ash amended soils

Abstract: Results indicated that there is no difference between rice samples grown in soils with or without fly ash. Studies also clearly indicated that there were no adverse effects on hematological, biochemical or histopathological parameters when rice was fed to rats for 6 months. This indicates that rice grown on fly ash treated soils may be safe for human consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…On the other hand, Nayak et al (2015) reported that the accumulation of heavy metals in rice grains in soils applied with 40% CFA in greenhouses was not significantly different from soils without CFA application. Moreover, the application of CFA at 200 t/ha did not result in the accumulation of Pb, Cd, As and Cr in rice samples, which were different from rice samples without CFA application (Bhaskarachary et al 2012). These results imply that the application of a relatively low amount of CFA did not lead to heavy metal accumulation in plants.…”
Section: Resultsmentioning
confidence: 77%
“…On the other hand, Nayak et al (2015) reported that the accumulation of heavy metals in rice grains in soils applied with 40% CFA in greenhouses was not significantly different from soils without CFA application. Moreover, the application of CFA at 200 t/ha did not result in the accumulation of Pb, Cd, As and Cr in rice samples, which were different from rice samples without CFA application (Bhaskarachary et al 2012). These results imply that the application of a relatively low amount of CFA did not lead to heavy metal accumulation in plants.…”
Section: Resultsmentioning
confidence: 77%
“…Usually, long grains have high amylose content and become dry and flaky on cooking and remain separate, while the short and medium grains have low amylose and are moist and firm on cooking and stick together (Bhaskarachary et al . ). From consumer perception, grains with low to intermediate amylose content are rather more liked.…”
Section: Introductionmentioning
confidence: 97%
“…Requirement of available K + for most field crops ranges from 60 to120 ppm . As most of the essential elements, potassium also shows paradoxical effect on plant physiology and growth; the low potassium levels results in restricted growth, reduced flowering, low yields and poor quality products, whereas high level of water soluble K + ions affects the germination of seeds and inhibit uptake of other useful minerals . Heavy crop production rapidly depletes the soils potassium and requires fertilizers to obtain crop yield of good quality.…”
Section: Introductionmentioning
confidence: 99%